Robust image hiding algorithm for secure multimodal biometrics - Yu-qiang CAO; Wei-guo GONG; Sen BAI (网络与信息安全学报)
In order to solve the bio-template secure transmission in multimode biometric authentication,a novel al-gorithm was presented that hiding face watermarks in fingerprint carrier image to improve security and recognition accuracy.RST invariant embedding region was obtained by carrier image normalization and the core point detection.Multiple embedding based on SVD in the region and watermark optimizations in extraction process were presented in hiding scheme.The security of the proposed algorithm and its robustness against different kinds of attacks were verified by simulations.